Management of coronary artery disease in patients with aortic stenosis in the era of transcatheter aortic valve replacement - Belur, Agastya D.; Solankhi, Naresh; Sharma, Ravi (Frontiers in Cardiovascular Medicine, 2023)
Aortic stenosis (AS) is a common valve disorder among the elderly, and these patients frequently have concomitant coronary artery disease (CAD). Risk factors for calcific AS are similar to those for CAD. Historically, the treatment of these conditions involved simultaneous surgical replacement of the aortic valve (AV) with coronary artery bypass grafting. Since the advancement of transcatheter AV therapies, there have been tremendous advancements in the safety, efficacy, and feasibility of this procedure with expanding indications. This has led to a paradigm shift in our approach to the patient with AS and concomitant CAD. Data regarding the management of CAD in patients with AS are largely limited to single-center studies or retrospective analyses. This article aims to review available literature around the management of CAD in patients with AS and assist in the current understanding in approaches toward management.